Analisis Tahapan Pemeriksaan Pembuktian dalam Hukum Acara Perdata di Indonesia dalam Putusan Mahkamah Agung Nomor 1666 K/PDT/2022 - Al Maksumiyyah , Alfi Zayyan (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
This article aims to analyze in depth the stages of evidentiary examination in civil procedural law in Indonesia. Evidence is a crucial element in the civil justice process, because its success greatly influences the judge’s decision. This research uses normative juridical methods with a statutory and regulatory approach, as well as analysis of legal doctrine and court practice. This article describes in detail each stage of evidence, starting from submitting evidence, evaluating the evidence by the judge, to the final decision. The results of the analysis show that the implementation of the evidentiary stages in Indonesia still faces challenges, especially related to the consistent application of legal principles by judges. This research provides recommendations to clarify procedures and strengthen judicial integrity in evidentiary examinations in civil cases